Construção do conceito infância: uma revisão histórico-crítica - Thiago, Idelvani da Conceição Bezerra (Brasil, 2022)
This research has the general objective of discussing the ideological construction of the concept of childhood from a historical-critical perspective in order to categorize and systematize research and main bibliographies on the subject, identifying the historical landmarks that comprise Brazilian childhood. The discussion demands an answer to the following questioning: What political, economic and social interests linked to the formulation of the concept of childhood made the term a hegemonic social construction in the capitalist system? The methodological organization was guided by the following specific objectives: a) to categorize in the repositories of theses and dissertations how the concept of childhood has been identified in academic lines, from the main bibliographies used; b) to systematize the concept of childhood once categorized in the research collected in the repositories, historically taking up the ideological factors behind the construction of this concept; c) identify the historical and political landmarks that corroborated the way of understanding childhood in Brazil. To achieve the objectives of the study, exploratory, selective, analytical and interpretive readings of texts and documents were carried out. Thus, we used a bibliographic research based on studies on childhood, by authors such as: Ariès (1986), Warde (2007), Klein (2012), Heywood (2004), Bernartt (2009), Kuhlmann Jr. and Fernandes (2012), Rizzini and Rizzini (2004), Rizzini and Pilotti (2011), Priore (1991; 2010) and Kuhlmann Jr. (1998). And the document analysis was carried out in the respective repositories: Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES); Digital Library of Theses and Dissertations UFAM (TEDE/UFAM). The theoretical foundation allowed us to conclude that the concept of childhood is a social construction, experienced by the concrete child, in a different way for each one. In view of this, childhood can present different conceptions depending on the time and place that the child is inserted. The analysis also showed that in each era, childhood received a different treatment, according to the political and economic ideals thought to the capitalist society that the bourgeoisie defends.